Understanding how aging experiences shape late career development - Ulrike Fasbender; Michela Vignoli; Gabriela Topa (The Career Development Quarterly, 2022)
Mature workers' aging experiences are central in transforming the self and as such can shape career-related outcomes, such as late career work engagement and motivation to continue working. We therefore investigate the relations between aging experiences (i.e., personal growth, gaining self-knowledge, social loss, and physical loss) and career-related outcomes. Moreover, we explore psychological capital as an adaptive set of resources that can explain how aging experiences are linked to mature workers' motivation to continue working and late career work engagement. We test our hypotheses using structural equation modeling based on two-wave data from a sample of 346 Spanish mature workers. Results showed that psychological capital mediated the positive effects of personal growth and gaining self-knowledge as well as the negative effect of social loss on career-related outcomes. By highlighting the links between mature workers' experiences, resources, and career-related outcomes, we contribute to a more profound understanding of late career development.
Keywords: 650; aging experiences; late career work engagement; motivation to continue working; older workers; psychological capital